Ketentuan Pelaksanaan Bimbingan Perkawinan Pada Masa Pandemi Covid-19 - Mohammad Adi Prasetiyo; Ahmad Hafid Safrudin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
Marriage is an event that has a very strong bond and must be fully guarded. In order for a marriage to last without divorce, a harmonious family is needed or commonly referred to as a sakinah mawaddah warahmah family. For this reason, in order to reduce divorce rates and increase families who are sakinah mawaddah warahmah, the Ministry of Religion has created a Marriage Guidance program (bimwin) or also called suscatin (bride candidate course) which is a short program that provides education and understanding about marriage for prospective brides and grooms. marry and live it in the future. This study uses a moderate qualitative approach. The type of research is field research. The results of the research that Marriage Guidance is a program from the Ministry of Religion as stated in the Decree of the Directorate General of Islamic Community Guidance (Dirjen BIMAS) Number 379 of 2018 which in this case must be submitted to the bride and groom. Given the importance of marriage guidance for prospective brides and grooms, KUA continues to provide guidance both before the pandemic and during the COVID-19 pandemic.